Primary Ewings Sarcoma of Kidney: A Case Report - Krishnendu Maiti; Akash Agrawal; Chhanda Datta; Dilip Kumar Pal (Journal of Clinical and Diagnostic Research, 2018)
Primary Ewings Sarcoma (EWS) of the kidney is a very rare tumour and very few cases have been reported till date. We present a case of a 36-year-old lady presenting to us with flank pain and haematuria, with a huge renal mass. Following left radical nephrectomy, histopathology was reported as ewings sarcoma. Hence, while dealing with renal masses in young patients, this entity should always be kept in mind.